Hallmark-guided subtypes of hepatocellular carcinoma for the identification of immune-related gene classifiers in the prediction of prognosis, treatment efficacy, and drug candidates - Guo, Chengbin; Tang, Yuqin; Yang, Zhao; Li, Gen; Zhang, Yongqiang (Frontiers in Immunology, 2022)
Hepatocellular carcinoma (HCC), accounting for ~90% cases of primary liver cancer, is a prevalent malignancy worldwide. The intratumor heterogeneity of its causative etiology, histology, molecular landscape, and immune phenotype makes it difficult to precisely recognize individuals with high mortality risk or tumour-intrinsic treatment resistance, especially immunotherapy. Herein, we comprehensively evaluated the activities of cancer hallmark gene sets and their correlations with prognosis of HCC patients using gene set variation analysis (GSVA), and identified two HCC subtypes with distinct prognostic outcomes. Based on these subtypes, seven immune-related genes were used to construct a novel prognostic gene signature (hallmark-guided subtypes-based immunologic signature, HGSIS) via multiple statistical approaches. The HGSIS-integrated nomogram suggested an enhanced predictive performance. Interestingly, oncogenic hallmark pathways were significantly enriched in the high-risk group and positively associated with risk score. Different mutational landscapes and immune profiles were observed between the high- and low-risk groups. Moreover, immunophenoscore (IPS) and tumor immune dysfunction and exclusion (TIDE) analysis showed different sensitivities of HGSIS risk groups for immune therapy efficacy, and the pRRophetic algorithm indicated distinguishable responses for targeted/chemo-therapies in different groups. KIF2C was picked out as the key target concerning HGSIS, and top 10 small molecules were predicted to bind to the active site of KIF2C via molecular docking, which might be further used for candidate drug discovery of HCC. Taken together, our study offers novel insights for clinically significant subtypes recognization, and the proposed signature may be a helpful guide for clinicians to improve the treatment regimens.